Pluripotent Stem Cell-Derived Hematopoietic Progenitors Are Unable to Downregulate Key Epithelial-Mesenchymal Transition-Associated miRNAs - Meader, Ellie; Barta, Tomas; Melguizo-Sanchis, Dario; Tilgner, Katarzyna; Montaner, David; El-Harouni, Ashraf A; Armstrong, Lyle; Lako, Majlinda (Stem cells (Dayton, Ohio), 2018)
Hematopoietic stem cells derived from pluripotent stem cells could be used as an alternative to bone marrow transplants. Deriving these has been a long-term goal for researchers. However, the success of these efforts has been limited with the cells produced able to engraft in the bone marrow of recipient animals only in very low numbers. There is evidence that defects in the migratory and homing capacity of the cells are due to mis-regulation of miRNA expression and are responsible for their failure to engraft. We compared the miRNA expression profile of hematopoietic progenitors derived from pluripotent stem cells to those derived from bone marrow and found that numerous miRNAs are too highly expressed in hematopoietic progenitors derived from pluripotent stem cells, and that most of these are inhibitors of epithelial-mesenchymal transition or metastasis (including miR-200b, miR-200c, miR-205, miR-148a, and miR-424). We hypothesize that the high expression of these factors, which promote an adherent phenotype, may be causing the defect in hematopoietic differentiation. However, inhibiting these miRNAs, individually or in multiplex, was insufficient to improve hematopoietic differentiation in vitro, suggesting that other miRNAs and/or genes may be involved in this process. Stem Cells 2018;36:55-64.
Keywords: buněčná diferenciace; miRNAs; Hematopoietic Stem Cells; Human embryonic stem cells; mikro RNA; Humans; Epithelial-mesenchymal transition; hematopoetické kmenové buňky; Pluripotent Stem Cells; lidé; Hematopoietic differentiation; pluripotentní kmenové buňky; Epithelial-Mesenchymal Transition; epitelo-mezenchymální tranzice; Cell Differentiation; down regulace; Down-Regulation; MicroRNAs